AD, Volume 14, n° 4, 1989 - Full Issue - journal system (Africa Development, 1989)
Table of Contents Popular Resistance in Tanzania: Lessons from the Sungu Sungu Horace Campbell .............................. 5 Crise Financière et Ajustement par le Marché dans le Monde Arabe: Quelles Perspectives Habib El Malki ............................... 45 Ghana Rice Policy: The Cost of Self-Sufficiency Samuel Asuming-Brempon ....................... 67 Prix officiels et Prix d'équilibre des Denrées alimentaires: le Cas du Maïs et du Mil à Lomé Mavor Tetey Agbodan ............................. 83 Class-Form ation, State Construction and Customary Law in Colonial Nigeria Ejembi Anefu Unobe ........................ 95 Publications Received ........................... 113